Suomen kielen hallinta ja sen kehitys Peruskoululaiset ja nuoret aikuiset - Pajunen, Anneli; Honko, Mari (Suomalaisen Kirjallisuuden Seuran Toimituksia, 2021)
The topic of the book is the incremental growth of linguistic knowledge from lexical to structural-cum-textual during the so-called later language development. Language mastery does not presuppose any acquaintance with prescriptive grammar but, instead, concerns the core of language which the so-called consensus principle applies to: the most frequent words and structures are mastered with certainty by everybody, but uncertainty increases as less frequent and more variable phenomena are taken into consideration. It is the goal of the study to make explicit the knowledge that is common to school children of different age groups, and to show how it develops both in its core and in its fringe areas. The mastery of less common aspects exhibits considerable statistical variation. The research embodies methodological pluralism insofar as it has been carried out by means both of the corpus method and the experimental method. Here experimental subsumes writing tasks, paper-and-pencil tests, and behavior under experimental conditions. The amount of participants native in Finnish varies from 300-2000. The book has a bipartite structure: mastery of meanings (Part I), and mastery of forms (Part II).